PEMBERDAYAAN UMKM KOPI LIBERICA DI DESA CIPASUNG MELALUI AGROWISATA DAN EDUKASI MANFAATNYA. - Indriyani, Oktavia; Salsabila, Dina; Fauzan, Raihan; Ridha, Mohammad; Nurizqy, Fara Fadya Azzahra; Mahardeka, Adelia Putri; Yumna, Farras Fida; Pradana, Muhammad Firyal; Zhafranudin, Muhammad Fakhri; Sumarto, Findi Amilia; Muslimah, Nur Annisa; Ramadhani, Shella; Fujiyanto, Fujiyanto; Izaz, Rofiq Khoirul; Wahadi, Wahadi; Senja, Nurul (LPPM Universitas Bina Bangsa, 2025)
Liberica coffee is one of the superior commodities in Cipasung Village, which has the potential to be developed through agritourism and community empowerment. However, Liberica coffee SMEs in this area face various challenges, including limited market access, processing technology, and product promotion. This study aims to optimize the potential of Liberica coffee SMEs by developing agritourism and Sharing Sessions with students from Universitas Swadaya Gunung Jati Cirebon. The research employs a qualitative descriptive approach through interviews, observations, and documentation studies. The results show that agritourism not only increases the economic value of coffee but also enhances community knowledge through direct visitor participation in the coffee production process. Additionally, Sharing Sessions with students provide insights into product innovation and marketing strategies. This holistic approach is expected to strengthen local economic sustainability and increase the competitiveness of Liberica coffee SMEs.